1995
DOI: 10.2169/internalmedicine.34.988
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism Associated with Multiple Myeloma.

Abstract: A 73-year-old womanwas diagnosed as primary hyperparathyroidism. Hypercalcemia recurred after parathyroidectomy, though serum calcium concentration temporarily resumed to normal. Hypercalcemiawas eventually shownto be due to multiple myeloma.In spite of the frequent association of hypercalcemia with malignant disease and the relative frequency of primary hyperparathyroidism as a cause ofhypercalcemia, primary hyperparathyroidism accompanied by multiple myelomahas been considered in only a limited number of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Therefore, the association between the 2 disorders is still controversial. [4][5][6][7][8][9][10][11] This prompted us to prospectively evaluate the prevalence of monoclonal gammopathies in patients with surgically proved PHPT.…”
mentioning
confidence: 99%
“…Therefore, the association between the 2 disorders is still controversial. [4][5][6][7][8][9][10][11] This prompted us to prospectively evaluate the prevalence of monoclonal gammopathies in patients with surgically proved PHPT.…”
mentioning
confidence: 99%
“…Either diagnosis does not exclude the other, and inadequate intervention may result in partially increased morbidity or mortality. Although the association of MM with I°HPT has been reported previously in 12 case reports (adenoma: 10 cases, hyperplasia:1 case) [1][2][3][4][5][6][7][8][9][10][11][12], only one case of this combination has been reported in Japan [12]. The mechanisms leading to the onset of I°HPT and MM in this patient are unclear.…”
Section: Discussionmentioning
confidence: 83%
“…Parathyriodectomy was necessary in 13 cases to achieve the eucalcemic state, and this study concluded that surgical treatment is indicated in these synchronous conditions to correct hypercalcemia (2).…”
Section: T a B L E 2 [ 2 -1 5 ] Re P O R T E D Ca S E S O F Co N C U mentioning
confidence: 83%
“…However, the occurrence of these two relatively common conditions in the same patient is rare (1) and has been reported only 17 times in the literature (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) d g l a n d , a h e t e r o g e n e o u s r o u n d ma s s t h a t me a s u r e s 1 . 1 × 1 .…”
Section: Introductionmentioning
confidence: 99%